The Influence Of Company Growth, Return On Asset (ROA), Leverage And Audit Opinion In The Previous Year On Acceptance Of Going Concern Audit Opinions (In Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange 2013-2017) - Kimsen, Kimsen; Pambudi, Januar Eky; Alamsyah, Sustari; Komariah, Kokom (Universitas Serang Raya, 2022)
The purpose of this study is to empirically examine the effect of several financial ratios on going-concern audit opinions. The factors tested in this study are company growth, return on assets, leverage and the previous year's audit opinion as independent variables, while going concern audit opinion as the dependent variable. The data used in this study is secondary data with the sampling method used is the purposive sampling method. This study uses 28 samples of property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2013-2017. The analytical tool used is panel data logistic regression analysis and processed with Eviews 9.0. The test results show that the previous year's audit opinion has no effect on going concern audit opinion, while company growth, return on assets, and leverage have no effect on going concern audit opinion.